1998
DOI: 10.1128/mcb.18.3.1611
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation of DNA Synthesis and Cell Division in Senescent Human Fibroblasts by Microinjection of Anti-p53 Antibodies

Abstract: In human fibroblasts, growth arrest at the end of the normal proliferative life span (induction of senescence) is dependent on the activity of the tumor suppressor protein p53. In contrast, once senescence has been established, it is generally accepted that reinitiation of DNA synthesis requires loss of multiple suppressor pathways, for example, by expression of Simian virus 40 (SV40) large T antigen, and that even this will not induce complete cell cycle traverse. Here we have used microinjection of monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 52 publications
4
115
0
3
Order By: Relevance
“…Thus, in agreement with the observations of others, senescent cells have the potential to escape the arrest and may even resume proliferation when any of the major control proteins such as p53 or pRb is inactivated. 1,2,35,37 Cells which lack p16INK4a, a frequent feature of tumor cells, seem to be prone to escape the arrest more efficiently. 38 The silent accumulation of DNA damage may increase the risk to select for spontaneous cell mt's, which can overcome the arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in agreement with the observations of others, senescent cells have the potential to escape the arrest and may even resume proliferation when any of the major control proteins such as p53 or pRb is inactivated. 1,2,35,37 Cells which lack p16INK4a, a frequent feature of tumor cells, seem to be prone to escape the arrest more efficiently. 38 The silent accumulation of DNA damage may increase the risk to select for spontaneous cell mt's, which can overcome the arrest.…”
Section: Discussionmentioning
confidence: 99%
“…The following antibodies were used: mouse monoclonal antibodies (mAbs) to p53 pAb240, pAb246, pAb248 and pAb421; [35][36][37] antibodies to cyclin D (M-20), cyclin E (M-20), cyclin A (H432), CDK2(D-12), p21(H164 and Sx118), p107 (sc-318), p130(Rb2) (sc-317), GFP (sc-8334 and sc-9996) from Santa Cruz Biotechnology (Santa Cruz, USA); CDK4 (H22) (Biomol, Hamburg, Germany); pRb(p105) (G3-245) (BD Biosciences, San Diego, USA), cleaved caspase 3 (Cell Signaling Technology), tubulin (Oncogene Research, San Diego, USA), cyclin A (C-4710) (Sigma, Munich, Germany), rabbit anti-lamin B. Incorporation of BrdU was monitored with a mouse mAb to BrdU (Boehringer Mannheim, Mannheim, Germany); normal goat serum and normal donkey serum were purchased from DAKO (Glostrup, Denmark); FITC-and Texas Red-conjugated secondary antibodies were from Jackson Immuno Research Laboratories (West Grove, USA). The plasmids used were: pcDNA3E1A12S (T Dobner, Regensburg, Germany) and pIRES2-AcGFP1-cycA.…”
Section: Antibodies and Expression Plasmidsmentioning
confidence: 99%
“…RNA interference-mediated suppression of CKIs efficiently triggered mitosis in terminally differentiated skeletal muscle cells, quiescent fibroblasts and senescent embryo kidney cells. Similarly, it has been shown that injection of anti-p53 antibodies or the acute removal of pRb can reactivate the cell cycle in senescent cells (Gire and Wynford-Thomas, 1998;Sage et al, 2003). Thus, these findings implicate that senescent growth arrest can not be reversed by known physiological signals, but upon restoration of TACC3 expression or depletion of mediators involved in checkpoint control, although Aurora-A kinase inhibition was reported to cause irreversible cell cycle arrest (Huck et al, 2010).…”
Section: Downregulation Of Tacc3 Induces Cellular Senescence S Schmidmentioning
confidence: 90%
“…We do know it is possible to reactivate the growth of some types of senescent cells by inactivating p53 (Gire and Wynford-Thomas, 1998;Beausejour et al, 2003). Cells that express the p16 tumor suppressor protein, which activates the pRB tumor suppressor, are refractory to reversal by p53 inactivation .…”
Section: Do Senescent Cells Promote Age-related Pathology?mentioning
confidence: 99%